Emergency remote teaching during the covid-19 pandemic: Experiences among Mexican university students - Alejandrina Bautista Jacobo; María Olga Quintana Zavala; Daniel González Lomelí (Apertura, 2023)
The aim of this research was to explore the experiences of emergency remote teaching (ERT) during the covid-19 pandemic among students at a public university in the northwest region of Mexico. A descriptive correlational exploratory cross-sectional study was conducted with a nonprobabilistic sample of 1550 students. A survey was designed and validated by experts, and it was implemented online using the Microsoft Forms platform. Findings revealed that more than half of the students demonstrated very good or excellent proficiency in virtual platforms. Additionally, 28% of women experienced a difficult or very difficult adaptation process to the platforms, while this percentage was lower among men (20.9%). Students expressed that the academic performance of their instructors during ERT ranged from average to good, but the majority indicated that instructors were not adequately prepared to conduct classes in this modality, since teaching through virtual platforms requires planning and designing strategies. Despite both teachers and students became familiar with digital tools during the pandemic, it is recommended to encourage synchronous digital environments for teachers and explore didactic strategies for asynchronous ones.